Atlas of Global Development A Visual Guide to the World's Greatest Challenges. (World Bank Atlas, 2013)
COMPLETELY REVISED AND UPDATED Published in association with Harper Collins, the completely revised and updated fourth edition of the Atlas of Global Development is a comprehensive guide to the most critical issues facing our changing world today. A visual guide to global issues -easy-to-read graphical presentation with every topic presented by colorful world maps, tables, graphs, and photographs Topics that are shaping our world - key development indicators, from poverty, population growth, and food production to climate change, foreign direct investment, and international trade The latest, authoritative statistics - from the World Bank?s World Development Indicators database The Atlas comes with an interactive companion online atlas, the new World Bank e-Atlas of Global Development, and new to this edition, a companion mobile app. 'This is an excellent, up-to-date source book which will be invaluable for students of, and staff teaching, higher levels of geography .... a clear, concise, easily-accessible and well-illustrated volume.' - Geographical Association, United Kingdom